THE PHENOMENON OF ANTONYMY IN PHRASEOLOGISMS EXPRESSING PATIENCE AND ENDURANCE - Raxmanova Sarvinoz Alisherovna (Innovate Conferences, 2025)
This article focuses on the study of antonymy in phraseologisms that describe the patience and endurance. Even though patience and endurance are linguistically related, they can create phraseological units which have contrary meanings in different situations. The article studies the semantic correlation of phraseologisms of patience and endurance and their antonyms. The study examines alterations in phraseologisms, their functions in social and cultural setting, and the importance of the phenomenon of antonymy in linguistics. This research enables comprehending deeper the semantic aspects of a given language and its phraseological systems, and also brings attention towards the process of developing antonymization during language acquisition.
Keywords: Patience, endurance, phraseology, antonymy, semantics, linguistics, phraseological units, language evolution, social context, linguistics.